The Academic Sabbatical A Voyage of Discovery - Sibbald, Timothy M.; Victoria, Handford (University of Ottawa Press, 2022)
The Academic Sabbatical: A Voyage of Discovery is a collection of narratives that reveals how important sabbaticals are to faculty and, by extension, to higher education. By taking an in-depth look at the diverse experiences and perspectives shared by its collaborators, this work provides significant evidence that academic sabbaticals are instrumental in increasing productivity in terms of research and knowledge dissemination, the essence of today's university studies. Thanks to these earned periods of self-directed focused work, scholars can restore their academic energies, which leads to enhanced program development, renewed dedication to graduate students, and intellectual sharing among peers. Although not without challenges and tensions, sabbaticals help academics build stronger and deeper connections, laying a solid foundation for future growth and achievement. While this book stands alone in promoting the richness and power of the sabbatical as a structural feature of the academy, it is a great follow-up to The Academic Gateway and Beyond the Academic Gateway, which discuss the tenure-track and tenure decision.The Academic Sabbatical: A Voyage of Discovery is a collection of narratives that reveals how important sabbaticals are to faculty and, by extension, to higher education. By taking an in-depth look at the diverse experiences and perspectives shared by its collaborators, this work provides significant evidence that academic sabbaticals are instrumental in increasing productivity in terms of research and knowledge dissemination, the essence of today's university studies. Thanks to these earned periods of self-directed focused work, scholars can restore their academic energies, which leads to enhanced program development, renewed dedication to graduate students, and intellectual sharing among peers. Although not without challenges and tensions, sabbaticals help academics build stronger and deeper connections, laying a solid foundation for future growth and achievement. While this book stands alone in promoting the richness and power of the sabbatical as a structural feature of the academy, it is a great follow-up to The Academic Gateway and Beyond the Academic Gateway, which discuss the tenure-track and tenure decision.